2002
DOI: 10.1002/ptr.854
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of Acorus calamus against acrylamide induced neurotoxicity

Abstract: Exposure of rats to acrylamide (ACR) caused hind limb paralysis in 58% of the animals on day 10 and decreased behavioural parameters, namely distance travelled, ambulatory time, stereotypic time and basal stereotypic movements compared with the control group. These rats also had a decrease in the reduced glutathione (GSH) content and glutathione-S-transferase (GST) activity in the corpus striatum and an increase in striatal dopamine receptors, as evident by an increase in the binding of 3H-spiperone to striata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(41 citation statements)
references
References 21 publications
(20 reference statements)
2
39
0
Order By: Relevance
“…Therefore, oxidant/antioxidant balance is spoiled, oxidative stress occurs and thereby, oxidative damage occurs in cells (1,14,(50)(51)(52). One study found that the level of thiobarbituric acid reactive products had increased signifi cantly in the liver samples taken from the rats administrated with acrylamide in acute dose.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, oxidant/antioxidant balance is spoiled, oxidative stress occurs and thereby, oxidative damage occurs in cells (1,14,(50)(51)(52). One study found that the level of thiobarbituric acid reactive products had increased signifi cantly in the liver samples taken from the rats administrated with acrylamide in acute dose.…”
Section: Discussionmentioning
confidence: 99%
“…These results show that acrylamide causes a signifi cant decrease in antioxidant parameters. Acrylamide especially decreases the GSH and GST activity levels of cells, spoils the oxidant/antioxidant balance against the oxidants and thus leads to oxidative damage in cells (1,14,(50)(51)(52)(55)(56)(57)(58).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, ACR exposure resulted in the central-peripheral neuropathy in humans (LoPachin, 2004) and in laboratory animals, including rats and monkeys (Seale et al, 2012). Shukla et al (2002) found hind limb paralysis in 58% of the rats treated with ACR for 10 d, which attributed to ACR neurotoxicity. El-Yamany and Bayomy (2007) concluded that the abnormal body posture, muscle weakness, and legs play accompanying ACR-intoxication in rats may be related to the degeneration of the brain monoaminergic system.…”
Section: Discussionmentioning
confidence: 99%
“…The levels of GSH content and GST activity increased in the corpus striatum, where as the dopamine receptors decreased compared with the AC-treated rats. The results proved that the neurobehavioral changes produced by acrylamide was prevented with the treatment by ACrhizomes (Shukla et al, 2002). The neuroprotective potential of ethanol:water (1:1) extract of rhizomes of AC was reported in middle cerebral artery occlusion (MCAO)-induced ischemia in rats.…”
Section: Behavorial Changesmentioning
confidence: 74%